2009
DOI: 10.1016/j.cplett.2009.07.100
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon absorption of perylene derivatives: Interpreting the spectral structure

Abstract: a b s t r a c tThis work investigates the two-photon absorption spectrum of perylene tetracarboxylic derivatives using the white-light continuum Z-scan technique. Perylene derivatives present relatively high two-photon absorption cross-section, which makes them attractive for applications in photonics. Because of the spectral resolution of the white-light continuum Z-scan, we were able to observe a well defined structure in the two-photon absorption spectrum, composed by two distinct peaks. These peaks, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
1
7
0
2
Order By: Relevance
“…two-photon lineshapes are completely different, indicating that the two different excitation modes access different states. A similar two-photon absorption line shape has been measured for PER, 46,47 and other workers have shown that PER derivatives have different one-and two-photon absorption spectra, 48,49 as expected for this class of highly symmetric molecules. In PP, the one-and two-photon spectra both exhibit similar vibronic progressions with spacings of ∼20 nm (corresponding to a 1000−1200 cm −1 vibrational mode characteristic of PAH's).…”
Section: ■ Experimental Sectionsupporting
confidence: 79%
“…two-photon lineshapes are completely different, indicating that the two different excitation modes access different states. A similar two-photon absorption line shape has been measured for PER, 46,47 and other workers have shown that PER derivatives have different one-and two-photon absorption spectra, 48,49 as expected for this class of highly symmetric molecules. In PP, the one-and two-photon spectra both exhibit similar vibronic progressions with spacings of ∼20 nm (corresponding to a 1000−1200 cm −1 vibrational mode characteristic of PAH's).…”
Section: ■ Experimental Sectionsupporting
confidence: 79%
“…It should be noted that PBI works as an efficient 2PA unit, and the maximum 2PA wavelengths of these PBIs were similar to the 640 nm reported for the fluorenylperylene-functionalized diimides. 20,43 Among them, PCB-PBI has a high δ 2PA value of ∼1890 GM, implying that the extension of total ICT efficiency and effective conjugation size leads to an obvious increase of δ 2PA values (Table S5). For consistently comparing the component contribution in this series, the normalization criterion based on the number of PBI units was set to obtain a relevant figure of merit.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This includes branched chromophore, prion peptide nanostructures, porphyrin macrocycles, and cyclothiophenes . Among the different macromolecules investigated for enhanced NLO and TPA properties, both perylene bisimides and thiophene dendrimers have gained intense interest for their promising potential in organic electronic device application. , …”
Section: Introductionmentioning
confidence: 99%
“…19 Among the different macromolecules investigated for enhanced NLO and TPA properties, both perylene bisimides and thiophene dendrimers have gained intense interest for their promising potential in organic electronic device application. 20,21 Perylene bisimide dyes (PBIs) have been developed in the past few years and are now one of the most useful classes of fluorescence materials. 22 PBI dyes exhibit exceptional water solubility, thermal stability, fluorescence intensity, and photochemical stability with high fluorescence quantum yields up to 0.99.…”
Section: Introductionmentioning
confidence: 99%